Refugees Who Arrive by Boat and Canada’s Commitment to the Refugee Convention: A Discursive Analysis - Mann, Alexandra (Refuge: Canada's Journal on Refugees, 2011)
This paper offers a comparative analysis of official discourse surrounding three incidents of asylum seekers arriving in Canada by boat: the Komagata Maru in 1914; the Sri Lankans who arrived in Newfoundland on lifeboats in 1986; and the Ocean Lady in 2009. The objective is to assess Canada’s commitment to protecting refugees at these three points in history and evaluate academic contentions that the concept of the refugee is being eroded. The selected incidents trace the emergence and decline of the notion of the refugee in Canadian official discourse. Even during the peak of Canada’s commitment to refugees in the 1980s, the discourse reveals blurriness between the ideas of the “refugee” and the “illegal migrant.” However, the characterization of asylum seekers as “illegals” is more intense now than in the earlier periods. This shift in the discourse warrants attention as we face the prospect of what Audrey Macklin describes as the “discursive disappearance of the refugee.”